Forgotten giants: new Anaxyelidae (Hymenoptera) from the Jurassic of Karatau - Kopylov, Dmitry S. (Zootaxa, 2018)
Three new species of Anaxyelidae from the Middle–Upper Jurassic of Karatau (Kazakhstan) are described: Brachysyntexis tenebrosa sp. nov., B. tigris sp. nov., and Kulbastavia grandis sp. nov. By the size of the body, B. tenebrosa and K. grandis are the largest Jurassic species of the family. In the Jurassic period, the Anaxyelidae were represented only by the subfamily Anaxyelinae. They were found in three localities: Daohugou (China, 17 specimens), Karatau (Kazakhstan, 27 specimens) and Khoutiyn-Khotgor (Mongolia, 1 specimen). A list of all known Jurassic findings of Anaxyelidae from the collections of the Palaeontological Institute (Moscow) is given.